Qualidade do leite, mastite subclínica, sensibilidade estafilocócica e uso de antimicrobianos em municípios do Norte de Minas Gerais - Vanessa Amaro Vieira (2012)
The purpose of this research was to verify the quality of raw milk in rainy and dry season, the presence of bovine subclinical mastitis, the Staphylococcus aureus sensitivity against antibiotics and the usage of these products in agricultural family units from northern Minas Gerais, Brazil. This research was carried out in 15 agricultural family units of Icaraí de Minas, Juramento and Montes Claros. Raw bovine milk samples were collected in dry and rainy seasons respectively, from August to October 2010 and from November 2010 to January 2011 for evaluation of the chemical composition and Somatic Cell Count (SCC). Twelve herds were selected because of the statistical homogeneity and the data were analyzed by the Tukey test. Antimicrobial residues in the milk of the 15 farms were examined and the subclinical mastitis diagnosis was carried out, the prevalence being evaluated by the chisquare test (2, p0.01). Coagulase positive S. aureus was isolated to verify in vitro sensitivity against antibiotics. To evaluate antibiotics usage, semistructured questionnaires were filled in. The average of milk fat and total solids was lower in Montes Claros and milk protein and lactose were superior in the rainy period. SCC was similar among places and periods and was within the law. Antimicrobial positive milk samples were 8.50% in all of the localities. The raw milk produced in agricultural family units of Icaraí de Minas, Juramento and Montes Claros showed chemical constituents inside the lawful standards, but the elevated SCC and the antibiotic residues presence can represent risks for public health. From 2,446 teats analyzed by the CMT, 636 (26.00%) were positive and 1,810 (74.00%) negative. In the periods of dry and rainy season respectively, 22.80 and 28.80% teats were positive to the CMT and subclinical mastitis was superior in the rainy period. Subclinical mastitis in Montes Claros was lower than in Juramento and Icaraí de Minas. Of the 80 and 198 strains isolated in the dry and rainy season respectively, 18(22.50%) and 50 (25.25%) were classified as S. aureus. The highestresistance was detected for cefadroxil, erythromycin and G penicillin.Subclinical bovine mastitis was detected and gentamicin and oxacillin were efficient against S. aureus isolated from milk of the herds in Icaraí de Minas, Juramento and Montes Claros. The disease for which most antibiotics are used was mastitis (93.33%). The CMT is the most employed method for diagnosis in Icaraí de Minas. Ten (66.66%) of those interviewed consulted their veterinarian prescriptions to buy antibiotics, 40.00% looked for the veterinary products store attendant, 13.33% followed their neighbors tips and 6.66% used by their own experience. Most producers reported following the antimicrobial drug leaflet information. Some of them said that they supplied the milk contaminated with antibiotic residues to calves and other animals. All respondents believed that milk with antibiotics is harmful to human health, butthey didnt know the reason. In agricultural family units of Icaraí de Minas,Juramento and Montes Claros mastitis control and prevention are necessary. Besides, the farmers need training about good antibiotics usage.